Perception of the human dignity concept in students at Universidad Pedagógica y Tecnológica de Colombia, Duitama branch (2014)
The research wonders from the critical theory of the human rights about the attributed meaning to the human dignity based on university students. The qualitative phase sought to understand the meanings attributed to dignity by University students from the UPTC in Duitama, through the development of 7 focus groups, involving 56 students analyzed for meaning units: dignity, university living as you like, living well, living without humiliation. For participants, human dignity means to know, to exercise human right, to enjoy human right, increase their value as human beings, while enjoying guarantees for the exercise of their human rights, meanwhile, the University as an institution means a setting that fosters human dignity, whenever human beings are the center of their function. The development of this research contributes to the overall education of the participants, when listen, socialize and discuss the different meanings attributed to human dignity in relation to the University.